2014
DOI: 10.3892/ol.2014.1996
|View full text |Cite
|
Sign up to set email alerts
|

The role of MALAT1 correlates with HPV in cervical cancer

Abstract: Cervical cancer, the second most common type of cancer in women worldwide, is responsible for >275,100 mortalities each year and is associated with high-risk human papilloma virus (HR-HPV). HPVs have two important oncogenes, E6 and E7, which have crucial roles in malignant transformation in cervical cancer. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a long non-coding RNA originally identified in non-small cell lung cancer. Previous studies have revealed that MALAT1 is expressed in numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 37 publications
1
78
0
Order By: Relevance
“…MALAT-1 may promote cell migration and decrease cell proliferation in CaSki cells. Notably, MALAT-1 may increase cell proliferation by upregulating cyclin D1, cyclin E and cluster of differentiation K6 (18). The study conducted by Wang et al indicated that MALAT-1 was overexpressed in GC cells (22).…”
Section: Molecular Targets Of Malat-1mentioning
confidence: 99%
See 3 more Smart Citations
“…MALAT-1 may promote cell migration and decrease cell proliferation in CaSki cells. Notably, MALAT-1 may increase cell proliferation by upregulating cyclin D1, cyclin E and cluster of differentiation K6 (18). The study conducted by Wang et al indicated that MALAT-1 was overexpressed in GC cells (22).…”
Section: Molecular Targets Of Malat-1mentioning
confidence: 99%
“…The study conducted by Jiang et al identified the correlation between MALAT-1 and human papillomavirus (HPV) (18). In this study, 64 cases of clinical cervical squamous cell carcinoma (SCC) samples were collected.…”
Section: Potential Clinical Applications Of Malat-1mentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of some lncRNAs has been reported to suffer important alterations in cervical cancer and has been associated with cancer progression and aggressiveness among the most notably are as follows: H19, HOTAIR, MALAT1, GAS5, MEG3, CCAT2 12, 13, 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%